Caribbean/Latin American relations : a framework for cooperation and collaboration. - Neil, Joan C. (UN/ECLAC Port of SpainTT, 1990)
Examines past initiatives in foraging closer links, as well as identifying common development priorities. Proposes an institutional framework for follow-up of a number of initiatives to promote greater regional interaction.